A inter-relação universidade-empresa: um estudo de caso referente à concessão de bolsas de pesquisa do Centro de Estudos Avançados em Segurança de Barragens (Ceasb) - Santos, Elida Suellen dos (2021)
The university-company interrelation intensifies the conditions that lead to innovation in a knowledge-based society. When considering the role of the University, and consequently its connection with the job market, the present study aims to present an analysis of the UniversityCompany interrelation in the professional training process, from the perspective of the granting of research grants from the Center for Advanced Studies in Dam Safety (CEASB), integrated intothe Itaipu Technological Park - Brazil. This is a case study of a qualitative and quantitative nature, which uses bibliographic and documentary research, Lattes and LinkedIn platforms, questionnaires and interviews as data collection techniques. The study demonstrates a perspective of academic extension from the experience of researchers inserted in the organizational context in an ecosystem that facilitates the interaction between different actors. The empirical results revealed the interaction of CEASB with 17 Higher Education Institutions and allowed the mapping of 312 ex-scholarship holders through document analysis. In addition, in the research, the platforms Lattes and LinkedIn were consulted and 280 ex-scholarship holders were located, making professional and academic diagnoses possible, identifying the individuals who are working, studying and their performance, as well as the limitations of the chosen method of analysis. In order to deepen the understanding of the topic, a questionnaire was applied, which reached 118 former-scholarship recipients, and interviews were carried out with the manager of CEASB and eight former-scholarship holders. The results of the questionnaire allowed us to confirm the profile of the ex-scholarship holders, in addition to identifying the main motivations for joining the CEASB, in which the possibility of acting and professional experience, receiving a scholarship and the possibility of act directly in projects related to Itaipu Binacional. The interview with the manager aimed to direct the script of the interviews carried out with the alumni to identify issues of interest to CEASB. With the results of the interviews, it was possible to explore the data from the application of the questionnaire and one can conclude the relevance of an environment such as the CEASB for the development of researchers through the granting of research grants, evidencing the mutual benefits of this relationship for the formation, professional development and the possibility of practical applications of knowledge acquired in academia.